2018
DOI: 10.1111/tpj.14002
|View full text |Cite
|
Sign up to set email alerts
|

JMJ30‐mediated demethylation of H3K9me3 drives tissue identity changes to promote callus formation in Arabidopsis

Abstract: Plant somatic cells can be reprogrammed by in vitro tissue culture methods, and massive genome-wide chromatin remodeling occurs, particularly during callus formation. Since callus tissue resembles root primordium, conversion of tissue identity is essentially required when leaf explants are used. Consistent with the fact that the differentiation state is defined by chromatin structure, which permits limited gene profiles, epigenetic changes underlie cellular reprogramming for changes to tissue identity. Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 46 publications
(91 reference statements)
0
46
0
Order By: Relevance
“…In A. thaliana, overexpression of LBD16, LBD17, LBD18, and LBD29 were enough to induce callus with a similar appearance to the callus induced on callus-inducing-medium (Fan et al, 2012). With the exception of the ARF transcription factor, WUSCHEL-related homeobox 11 (WOX11) and JUMONJI C DOMAIN-CONTAINING PROTEIN 30 (JMJ30) can also regulate the LBD genes in A. thaliana (Liu et al, 2014;Lee et al, 2018). It was reported that LBD proteins interact with the basic leucine zipper (bZIP) transcription factor to promote callus formation (Xu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In A. thaliana, overexpression of LBD16, LBD17, LBD18, and LBD29 were enough to induce callus with a similar appearance to the callus induced on callus-inducing-medium (Fan et al, 2012). With the exception of the ARF transcription factor, WUSCHEL-related homeobox 11 (WOX11) and JUMONJI C DOMAIN-CONTAINING PROTEIN 30 (JMJ30) can also regulate the LBD genes in A. thaliana (Liu et al, 2014;Lee et al, 2018). It was reported that LBD proteins interact with the basic leucine zipper (bZIP) transcription factor to promote callus formation (Xu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that submergence epigenetically regulates the OPR3 gene to inactivate gene expression before wounding. To find genes responsible for submergence-mediated histone modifications, we analysed expression of the OPR3 gene in the mutants that are deficient in a histone deacetylase ( axe1-5 ) 44 , a histone demethylase ( jmj30-2 ) 45 , and histone methyltransferases ( atx1-2 atx2-1 ) 46 . However, expression of the OPR3 gene in these mutants was similar to that in Col-0 seedlings (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Auxin accumulation in the founder cells mediates degradation of IAA14/SLR, which releases ARF7 and ARF19 that upregulate LBD16-18 and LBD29, involving ATXR2-mediated H3K36me3 deposition [ 4 , 41 , 42 ]. JUMONJI C DOMAIN-CONTAINING PROTEIN 30 (JMJ30) also associates with the ARF-ATXR2 complex to promote LBD expression by removing repressive H3K9me3 marks [ 43 ], while the BRASSINOSTEROID INSENSITIVE 2 (BIN2) kinase integrates temperature sensitivity into this cascade by enhancing the transcriptional activity of ARF7&19 and LBD genes [ 44 ]. In turn, LBD18 reinforces the auxin signal by promoting ARF7&19, and, together with LBD33, it triggers cell proliferation via transcriptional activation of E2 PROMOTER BINDING FACTOR a ( E2Fa ), which associates with DIMERIZATION PARTNERs (DPs) to stimulate DNA replication genes [ 7 , 11 ].…”
Section: Cellular and Molecular Framework Of De Novo Shoot Organogmentioning
confidence: 99%